2008
DOI: 10.1016/j.jnutbio.2007.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol inhibits methionine adenosyltransferase II activity and S-adenosylmethionine biosynthesis and enhances caspase-3-dependent cell death in T lymphocytes: relevance to alcohol-induced immunosuppression

Abstract: An important aspect in alcohol abuse associated immune suppression is the loss of T helper CD4 + lymphocytes leading to an impairment of multiple immune functions. Our work has shown that ethanol can sensitize CD4 + T lymphocytes to activation-induced, caspase-3 dependent cell death (AICD). It has been demonstrated that formation of S-adenosylmethionine (SAMe) catalyzed by methionine adenosyltransferase II (MAT II) is essential for CD4 + T cell activation and proliferation. Since ethanol is known to affect SAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Furthermore, it is reasonable to suppose that while EtOH and high‐fat or choline deficiency diets all affect the methionine metabolic pathway, there may be salient differences between which enzymes are being affected by these diets and hence responses to creatine supplementation. However, such comparisons are difficult to do at this time because such detailed analyses on the effects on the methionine metabolism as performed for EtOH exposure by us and others (Hote et al., ; Ji et al., ; Jung et al., ; Kharbanda, , ; Kharbanda and Barak, ; Kharbanda et al., ; Lu et al., ; Villanueva and Halsted, ) have not been performed for these other liver injury models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is reasonable to suppose that while EtOH and high‐fat or choline deficiency diets all affect the methionine metabolic pathway, there may be salient differences between which enzymes are being affected by these diets and hence responses to creatine supplementation. However, such comparisons are difficult to do at this time because such detailed analyses on the effects on the methionine metabolism as performed for EtOH exposure by us and others (Hote et al., ; Ji et al., ; Jung et al., ; Kharbanda, , ; Kharbanda and Barak, ; Kharbanda et al., ; Lu et al., ; Villanueva and Halsted, ) have not been performed for these other liver injury models.…”
Section: Discussionmentioning
confidence: 99%
“…This lowering of the hepatocellular SAM:SAH ratio is primarily because of the EtOH‐induced reduction in the level and activity of methionine synthase, an enzyme of the methionine metabolic pathway that remethylates homocysteine (and thus remove SAH) to generate methionine, the precursor for SAM (Kharbanda and Barak, ). Furthermore, EtOH administration has also been reported to decrease the transcript level and activity of methionine adenosyltransferase (an enzyme that catalyzes the generation of SAM) and reduce the expression of SAH hydrolase, the enzyme responsible for the reversible hydration of SAH into adenosine and homocysteine (Hote et al., ; Lu et al., ; Villanueva and Halsted, ). Hence, we feel it is primarily the EtOH‐induced changes in the expression and activities of the enzymes which regulate SAM and SAH levels, rather than GAMT‐catalyzed reactions that impose a considerable metabolic burden on methyl group metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This was thought to be necessary to provide a source of polyamine biosynthesis, and if AdoMet accumulation is prevented, lymphocyte activation was inhibited (57). More recently, Barve and colleagues (95) found that ethanol inhibited MAT2A transcription to result in lower MAT II activity and AdoMet level in T lymphocytes. This sensitized the CD4 + T lymphocytes to caspase-3-dependent activation-induced cell death and may be one of the explanations for alcohol-induced immune suppression (95).…”
Section: Role Of Adomet Outside Of the Livermentioning
confidence: 99%
“…More recently, Barve and colleagues (95) found that ethanol inhibited MAT2A transcription to result in lower MAT II activity and AdoMet level in T lymphocytes. This sensitized the CD4 + T lymphocytes to caspase-3-dependent activation-induced cell death and may be one of the explanations for alcohol-induced immune suppression (95). The same group of investigators also found that proliferating and transformed T leukemic cells express higher MAT II activity, and inhibiting MAT II expression in these cells resulted in higher caspase-8-dependent apoptosis (101).…”
Section: Role Of Adomet Outside Of the Livermentioning
confidence: 99%
“…Notably, elevated serum levels of soluble FasL and Fas that correlate with the decline in CD4+ T cells are observed in individuals with a history of alcohol abuse (15). Our earlier work has shown that in vitro exposure of human CD4+ T cells to physiologically relevant concentrations of ethanol increases their susceptibility to Fas-and activation-induced apoptotic death (16, 17). Hence, elucidating the mechanisms that govern FasL expression in normal as well as alcohol exposed CD4+ T cells is highly relevant in understanding the regulation of AICD and overall immune responses under both normal and pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%